Amomum tsaoko flavonoids attenuate ulcerative colitis by inhibiting TLR4/NF-κB/NLRP3 signaling pathway and modulating gut microbiota in mice - Huang, Zelin; Zhao, Yan; Yang, Weixing; Duan, Chunfen; Sheng, Jun; Tian, Yang; Peng, Lei; Gao, Xiaoyu (Frontiers in Microbiology, 2025)
Ulcerative colitis (UC) is a global disease for which there is little of effective treatment options, thus creating an urgent need for the development of new drug candidates from natural and functional foods. Amomum tsaoko Crevost et Lemarie is a kind of medicinal and food herb that is rich in flavonoids. However, the pharmacological effects of Amomum tsaoko flavonoids (ATF) on UC have not yet been reported. The present study established a mouse model of UC using 3% dextran sulfate sodium (DSS), and modern molecular biology techniques such as IHC, RT-qPCR, Western blot, and 16S rRNA gene analysis were used to investigate the effect of ATF in UC mice. The results demonstrated that a high dose of ATF (100 mg/kg) led to a significant restoration of body weight, disease activity index score, and colon length, in addition to ameliorating colonic tissue damage in UC mice. ATF reduced the serum levels of lipopolysaccharides (LPS), inhibited the activation of the colonic TLR4/NF-κB/NLRP3 signaling pathway, and increased the mRNA expression of tight junction proteins such as ZO-1, Occludin, and Claudin4. Furthermore, ATF was found to reduce the relative abundance of the DSS-induced conditional pathogenic (Escherichia-Shigella, Colidextribacter, and Oscillibacter), increase the potential probiotic taxa (Akkermansia, Bifidobacterium and unclassified_f__Atopobiaceae). Interestingly, these genera were found to be significantly correlated with the UC core phenotypic indicators. These findings indicated that ATF may alleviate UC symptoms by modulating the gut microbiota-LPS/TLR4/NF-κB/NLRP3 axis. The present study has the potential to serve as a valuable reference point for understanding the role of natural flavonoids in the prevention of inflammatory diseases, and to expand the future applications of ATF in the fields of food and medicine.